Social Solidarity and Public Vigilance Pertaining to Terrorist Activities in Peshawar, Pakistan - ume habiba; Perveen, Musrat (Journal of Peace, Development and Communication, 2023)
Terrorism is one of the most crucial and gravest issues in the global world including Pakistan. Different factors contribute to the outgrowth of terrorism but the most significant events of the Iranian Islamic revolution and civil war in Afghanistan were responsible for the genesis of religious and transnational based terrorism in Pakistan. The current research explored the role of social solidarity and public vigilance in combating terrorist activities in Peshawar city. The researchers developed a research hypothesis by using positivism as a research paradigm. The quantitative research lens were employed and respondents were selected by utilizing adaptive sampling to conduct surveys in different areas of Peshawar city that were affected due of terrorist attacks.The sample size comprises 384 respondents. The sample was selected based on the proportion of eyewitnesses and survivors from four strata. The self-administrated questionnaire aided to collect data from the field. The gathered data were analyzed by using SPSS. In crux, social solidarity and public vigilance are weaker among inhabitants of Peshawar to tackle terrorist activities.